RULE OF LAW PRINCIPLES: THE IMPLEMENTATION OF SOCIAL WELFARE IN INDONESIA - Risma Rosa Karunia; Eny Kusdarini (SOSIOEDUKASI, 2025)
The concept of the modern state of law not only emphasizes the rule of law, but also makes law an instrument to realize social justice and people's welfare. Indonesia as a state of law based on Pancasila has a constitutional responsibility to ensure public welfare as mandated in the Preamble to the Constitution of the Republic of Indonesia in 1945. This research aims to analyze the implementation of the principles of the modern state of law in the implementation of social welfare in Indonesia. This study uses a qualitative method with a normative juridical approach. Data was obtained through literature studies on relevant primary and secondary legal sources, then analyzed qualitatively. The results of the study show that Indonesia has adopted the principle of a modern state of law through social policy, namely Law Number 11 of 2009 concerning Social Welfare. However, its implementation still faces obstacles to law enforcement and social inequality. Therefore, the law needs to be directed in a substantive and humanist manner to realize the ideals of a Pancasila Law State that is socially just for all Indonesian people.